2010
DOI: 10.1515/hf.2010.041
|View full text |Cite
|
Sign up to set email alerts
|

Mixed mode fracture testing of adhesively bonded wood specimens using a dual actuator load frame

Abstract: An experimental evaluation of mixed mode fracture tests conducted on adhesively bonded wood specimens using a dual actuator load frame is presented. This unit allows the fracture mode mixity to be easily varied during testing of a given specimen, providing improved consistency, accuracy, and ease of testing over a range of loading modes. Double cantilever beam (DCB) type specimens made of southern yellow pine (Pinus spp.) wood substrates bonded with a commercially available one part polyurethane adhesive were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…SBT and CBT assume that the elastic characteristics of the adherend and adhesive materials are independent of the crack length. The accuracy of this assumption is deemed to be confi rmed by the coeffi cient of correlation, R 2 , of the CBT data fi t. The R 2 value obtained experimentally for CBT and ECM is often very near unity, even in materials with intrinsic variability such as wood (Gagliano and Frazier 2001 ;Nicoli et al 2009 ;Singh et al 2010 ), masking any possible effects of adherend variability. Nevertheless, Ic data for bonded wood specimens are often characterized by larger scatter (Triboulot et al 1984 ;Singh et al 2010 ;Nicoli et al 2012a ) than seen for uniform adherends, raising a question about errors introduced by methods recommended in the standards that were developed for uniform properties.…”
Section: Review Of Common Analysis Methods For Mode I Fracturementioning
confidence: 99%
“…SBT and CBT assume that the elastic characteristics of the adherend and adhesive materials are independent of the crack length. The accuracy of this assumption is deemed to be confi rmed by the coeffi cient of correlation, R 2 , of the CBT data fi t. The R 2 value obtained experimentally for CBT and ECM is often very near unity, even in materials with intrinsic variability such as wood (Gagliano and Frazier 2001 ;Nicoli et al 2009 ;Singh et al 2010 ), masking any possible effects of adherend variability. Nevertheless, Ic data for bonded wood specimens are often characterized by larger scatter (Triboulot et al 1984 ;Singh et al 2010 ;Nicoli et al 2012a ) than seen for uniform adherends, raising a question about errors introduced by methods recommended in the standards that were developed for uniform properties.…”
Section: Review Of Common Analysis Methods For Mode I Fracturementioning
confidence: 99%
“…Experience with southern yellow pine [110] and yellow poplar [109,119] has indicatively shown that typical values of G c for mode I tests are in the order of few to several hundreds Joules per square meter, whereas for other structural materials such as bonded steel and aluminum, values in the order of thousands Joules per square meter are not unusual. Without going too much into the detail of the quantitative results of fracture tests in different material systems, a general pattern that one can usually see for bonded wood specimens is that G c data are characterized by data scatter that is commonly higher than what is obtained in homogeneous materials also when failure occurs within the adhesive layer.…”
Section: Analysis Of Fracture Data Of Bonded Woodmentioning
confidence: 99%
“…Given the influence of a large number of factors and the fact that wood is a natural material, it is commonly found that fracture measurements taken on wood and bonded wood are characterized by data spread that is usually larger than the corresponding values obtained when testing more uniform adherends [107][108][109][110]. In particular, Triboulot et al [111] indicated with experimental and numerical studies that the high variability in wood properties requires researchers to deal with extensive statistical analysis when critical fracture toughness values are to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture measurements taken on wood and bonded wood joints are characterized by data spread that is usually larger than what is obtained when testing more uniform adherends (Ebewele et al 1979(Ebewele et al , 1980Triboulot et al 1984 ;Gagliano and Frazier 2001 ;Conrad et al 2003 ;Singh et al 2010 ). This fi nding has often been associated with random variations of properties that are diffi cult to detect in a natural material, but there are also morphological aspects that can possibly be accounted for.…”
Section: Introductionmentioning
confidence: 99%